Small extracellular vesicles in multiple myeloma development & drug resistance 1 - Menu, Eline (Henry Stewart Talks, 2025)
Diagnosis of multiple myeloma, Treatment of multiple myeloma and drug resistance, Exosomes/Small extracellular vesicles (sEVs), Role of sEVs in angiogenesis, Role of sEVs in osteolysis